Oil-Driven Consumption in Rentier Economies: Evidence from a Proxy-Based MPC Model in the Gulf Cooperation Council - Ebadi, Esmaeil; Balcilar, Mehmet; Are, Wasiu (International Journal of Energy Economics and Policy, 2025)
This study proposes a novel macroeconomic approach, specifically formulated to estimate the Marginal Propensity to Consume (MPC) in Gulf Cooperation Council (GCC) economies, based on high-frequency commodity price and trade data. As there are no reliable household consumption datasets, U.S. imports are used as a proxy for consumption, while crude oil prices serve as an instrument for measuring income. Controls are included for the American Consumer Price Index (CPI), bilateral exchange rates, and international uncertainty, as measured by the Volatility Index (VIX). Estimation via a fixed effects pooled panel regression model, covering the period from January 1992 to April 2025, yields an estimated MPC of 0.68. Controlling for demographic variations—specifically, expatriation induced lower consumption rates—the population-weighted adjustment yields a citizen MPC close to 1.0. Additionally, simulation analysis reinforces model robustness by demonstrating uniform and proportionate import responses to crude oil price shocks. These findings have significant implications for shaping fiscal policy decisions and macroeconomic forecasting in energy-exporting economies that struggle to utilize microdata, while also serving as a valuable tool for policymakers and researchers. Moreover, this novel macroeconomic model, with its forward-looking features, has significant potential to predict the demand-side effects of energy price volatility and inform adaptive and equitable energy policy decisions in the context of the GCC region.